The Use of English in User Experience Writing - Abdu Nur Ilham (Jurnal Vokasia, 2025)
This study explores the role and effectiveness of English in User Experience (UX) writing, particularly in the context of digital products aimed at international audiences. As global digital platforms increasingly adopt English to ensure accessibility and clarity, the integration of well-structured English UX writing has become essential in enhancing user interaction, engagement, and overall satisfaction. This study is based on the author’s internship experience at HiColleagues, an EdTech and IT service startup, where English was employed as the primary language for developing bilingual website content targeting B2B segmentation. Through qualitative analysis and practical implementation, the study investigates how English UX writing supports intuitive user navigation, improves comprehension, and contributes to the company's strategic goals such as increasing website traffic and attracting international leads. The study also outlines the stages involved in the UX writing process, including synergy meetings, drafting, revising, editing, and publishing. The findings highlight that the use of clear, concise, and context-aware English in UX writing not only enhances usability but also strengthens brand credibility in global markets. This thesis contributes to the growing body of knowledge in UX and content strategy, emphasizing the strategic importance of language in digital communication.